Settlement mapping analysis as land use change monitoring in Bogor Regency sub urban area - Merlina, Merlina (EDP Sciences, 2023)
Settlements are one of the basic human needs that need to be fulfilled. The development of settlements has implications for changes in land use. The high urban population affects the need for settlements in East Cilebut Village as a suburb area which is included in the peri-urban area. East Cilebut Village has the highest population density in Sukaraja District. Physical changes to the area in East Cilebut Village occurred in 2015 and 2020 with the emergence of new settlements. The research was conducted as a form of monitoring the changes in land use into settlements in East Cilebut Village. Monitoring was carried out by mapping settlement blocks in 2015 and 2020. The growth of settlement area was identified through Google Earth satellite imagery in 2015 and 2020. Data processing techniques were carried out by interpreting and on-screen digitizing satellite imagery using ArcGIS. The results of data processing were analyzed descriptively by presenting the data in the form of graphs and maps. Changes in settlement area occurred from 2015 to 2020. The settlement area in 2020 was higher than 2015. The results of data processing are expected to provide advice on settlement development policies for the local government. © 2023 EDP Sciences. All rights reserved.